PENERAPAN KNOWLEDGE MANAGEMENT PADA PROGRAM INNOVATION DAY DIREKTORAT DIGITAL BUSINESS PT TELKOM INDONESIA KOTA BANDUNG - Dinata, Aliya Rhamadhona; Sukoco, Iwan (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The digital era encourages every company to adapt to continue to grow and develop. Telkom's Digital Business Directorate is a digital locomotive for PT. Telkom Indonesia (Persero) Tbk. In competitive competition, Knowledge Management is needed as a form of HR management, because HR is a resource that cannot be imitated and duplicated. This research aims to determine and analyze the implementation of Knowledge Management activities in the Innovation Day program of the Digital Business Directorate of PT Telkom Indonesia, Bandung City. The object of this research is Knowledge Management activities in the Innovation Day program. The method in this research is a qualitative method with a descriptive research type. Data comes from in-depth interviews, observations, and documentation related to Knowledge Management activities in the Innovation Day program. The results of this research show that the overall implementation of the activity has gone well. However, the broadcasts presented as a form of knowledge sharing still prioritize the quantity of broadcasts and have not prioritized the quality of the content or the quality of the sources. Growth in terms of awareness is good, but the enthusiasm of Telkom DDB employees, especially for speakers who want to share knowledge, still needs to be improved. Sharing weekly knowledge through digital media such as websites and YouTube, utilizing digital trends, using social media to expand awareness, and holding quizzes with prizes to increase audience enthusiasm have been achieved under the objectives of the Innovation Day program.